Between Acceptance and Rejection: How Gender Influences the Implementation Climate of a School Sexuality Education Program - Torres-Cortés, Betzabé; Leiva, Loreto; Antivilo-Bruna, Andrés; Zavala-Villalón, Gloria (Frontiers in Education, 2021)
The implementation climate is the shared reception of the individuals involved in the intervention; it is a fundamental determinant of the success of program implementation. One of the factors that affects the implementation climate is gender, since it can influence the commitment of the participants toward sexuality education. This study aims to identify the implementation climate for students who receive a school sexuality education program and explore whether their gender is related to the acceptance of the intervention. A selective quantitative method was used, and a survey was designed to measure implementation climate. A confirmation factorial analysis (CFA) using Mplus 7.0 was conducted to establish the structure of the instrument. A cluster analysis was performed to determine levels of implementation climate. To measure the association between participants’ gender and the implementation climate, a Chi-square analysis was performed between each cluster, the gender of the students and each cluster and the type of school (single-sex girls’ schools, single-sex boys’ schools and co-educational schools). The results demonstrated four levels of implementation climate: acceptance, receptivity, conflict and rejection. Significant differences were observed in the relationship between these levels and the gender of the participants. Acceptance was associated with single-sex girls’ schools and female students, conflict and rejection were associated with a single-sex boys’ schools and male students, and co-educational schools were associated with conflict. This shows that there is a relationship between the different levels of the implementation climate and the gender.